posted by BOB on .
Balance the following equation for a half reaction that occurs in basic solution. Use e– as the symbol for an electron.
SO3^2- ---> S2O4^2-
I shall be glad to help you through this but you need to learn to do these yourself. I do these the looong way. The first step is to determine the oxidation step of each element. I will help you here. S on the left is +4 and on the right is +6. Add electrons to the appropriate side to balance the change in oxidation number.
SO3^2- ==> SO4^2- + ?e
H2O + SO3^2- ---> SO4^2- +2H^+ + 3e^-
Nevermind I figured it out its:
2SO3^2- + 2H2O + 2e^- ---> S2O4^2- + 4OH^-
You changed SO4^2- on the right to S2O4^2- and you can't do that. Also you have the e on the wrong side. Other than that it is ok.
2OH^- + SO3^2- ==> SO4^2- + 2e + H2O
DrBob222 you're wrong.
2 SO3^-2 + 2 H2O + 2e- -> S2O4^-2 + 4OH-